Low-power HF microelectronics a unified approach - Machado, Gerson A. S. (London, United Kingdom Institution of Engineering and Technology, 1996)
The book is organised in four parts, with generous contributions covering: (i) process/TCAD technology; (ii) device modelling/characterisation and circuit simulation; (iii) reliability and testability; (iv) analog and digital circuit and system design. In modern low-power HF microelectronics, the interaction needed between these parts to achieve the desired system performances means that frequently there will be an alliance and/or overlap among them. It is fundamental to high-yield successful manufacturing to relate in a quantitative manner the sensitivity of the electrical performance of the final devices and/or circuits to variations in structural parameters, doping profiles, layout, thermal effects and design.
Electronic reproduction.
Keywords: Microelectronics; Electronic books